The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/sle.0000000000000530
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticojejunostomy Versus Pancreaticogastrostomy After Pancreaticoduodenectomy: An Up-to-date Meta-analysis of RCTs Applying the ISGPS (2016) Criteria

Abstract: The goal of our study was to compare the impact of pancreaticogastrostomy (PG) versus pancreaticojejunostomy (PJ) on the incidence of complications after pancreaticoduodenectomy. A systematic search was performed using RevMan 5.3 software. A meta-analysis showed that PG was not superior to PJ in terms of postoperative pancreatic fistula (POPF). In multicenter randomized controlled trials, the incidence of POPF was lower in patients undergoing PG than in those undergoing PJ. However, PG was associated with an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 35 publications
5
49
2
Order By: Relevance
“…Of the several available techniques, pancreaticogastrostomy (PG) and pancreatojejunostomy (PJ) are the most commonly performed. Some RCTs[28-35] and meta-analyses[36-44] have compared PG and PJ. Topal et al[32] reported comparative results of the occurrences of POPFs (grade B or C) in an RCT with 329 patients.…”
Section: Pancreaticoduodenectomymentioning
confidence: 99%
See 1 more Smart Citation
“…Of the several available techniques, pancreaticogastrostomy (PG) and pancreatojejunostomy (PJ) are the most commonly performed. Some RCTs[28-35] and meta-analyses[36-44] have compared PG and PJ. Topal et al[32] reported comparative results of the occurrences of POPFs (grade B or C) in an RCT with 329 patients.…”
Section: Pancreaticoduodenectomymentioning
confidence: 99%
“…Several meta-analysis results on this issue have been reported and demonstrated the apparent superiority of PG in the risk for POPF despite the slight difference in the included studies[36-44]. However, PJ was found to have physiological advantages compared to PG although the follow-up periods were relatively short[34,45-48].…”
Section: Pancreaticoduodenectomymentioning
confidence: 99%
“…Surgical mortality rates have declined following advances in surgical techniques and the perioperative care associated with PD. However, the complexity of the surgical procedure leads to considerable morbidity after PD 2,3. With the increase in life expectancy in the fast-growing population of elderly patients, pancreatic procedures are increasingly being performed in this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…These risk factors can be categorized into 3 groups: The technically demanding group, intraoperative volume status–related group, and poor general condition group (Figure 2 ). The risk factors in the technically demanding group (soft pancreas[ 2 , 5 , 6 , 9 ], small pancreatic duct[ 6 , 9 , 29 ], extrapancreatic lesion[ 6 ], absence of preoperative pancreatitis or low lipase level[ 30 ], absence of preoperative endoscopic biliary decompression, absence of neoadjuvant radiotherapy, and high BMI[ 7 ]) indicate potential difficulty in reconstructing the pancreatic-enteric anastomosis, which could cause POPF. Patients with pancreatic cancer, chronic pancreatitis, or neoadjuvant treatment have increased pancreatic fibrosis and a lower incidence of POPF than other PD patients[ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this way, we expect our platform to help select patients who need more intense therapy and establish effective (and cost-effective) treatment strategies for POPF. Various mitigation strategies have been proposed to reduce the occurrence and morbidity of POPF, including technical variations, such as, pancreaticogastrostomy reconstruction[ 2 , 42 ], dunking/invaginating anastomosis[ 1 , 43 , 44 ], absorbable mesh patches[ 45 , 46 ], and the use of intraperitoneal drains[ 29 ], anastomotic stents[ 47 ], and prophylactic somatostatin analogues[ 4 , 48 , 49 ]. As a part of those efforts, we have an ongoing trial of this risk score wherein we are applying a somatostatin analogue during postoperative days 0–3 in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%